Cinema Africa 2019 - Interview A. Dao "Cooperation with Henry" (short clip 5) (Cinema Africa 2019, 2020)
The film festival of the Africa Multiple Cluster of Excellence "Cinema Africa" took place in November 2019. During the course of 4 days it showed four extraordinary films with African context. In this interview the producer Abdoulaye Dao talked with Nathalie Röthlingshöfer about this year's contribution "Duga, Les Charognards" from Burkina Faso. Cinema Africa 2019 was the 11th edition of the renowned Bayreuth African Film Festival. It has been founded and is curated by Prof. Dr. Ute Fendler.